The dynamics of the cytokine profile of the lungs and liver of BALB/C male mice infected with the H1N1 subtype avian influenza virus - Sataieva, Tatiana; Malygina, Veronika; Kriventsov, Maxim; Gurtovaya, Anna; Davydova, Alexandra; Kakharov, Amal (Edelweiss Applied Science and Technology, 2024)
The increasing number of reported cases of direct transmission of avian influenza viral strains to humans is obviously associated with the threat of a new pandemic and the need for a more detailed study of the pathogenesis of the viral infectious process. The aim of the research was to study the pathogenesis of influenza infection and in particular to establish the role of proinflammatory cytokines in the pathogenesis of the inectious process caused by influenza virus subtype A/WSN/1/33(H1N1). The experiment involved 21 male BALB/c mice aged 4-6 weeks weighing 16-18 g, which16were infected intranasally with influenza A/WSN/1/33(H1N1) virus under ether anesthesia by inoculation of 50 µl of allantoic fluid containing 10 LD50 of the virus. Histological studies were performed on samples of lung and liver tissues. It was evidenced that infection caused by the highly pathogenic for mice influenza virus A/WSN/1/33(H1N1) initiates the spreading of dystrophic and necrotic processes mainly in the lungs and liver. This can occur due the increase of proinflammatory cytokines leading to the violation of the circulatory system triggered by the active reproduction of the virus and toxic manifestations on behalf of cellular immunity. Structural changes in the lung and liver tissues of mice experimentally infected with the influenza A/WSN/1/33(H1N1) virus indicated the presence of a large amount of the virus at all stages of the experiment that requires further research.